Temperature dependent structural studies and magnetic properties of BaCa2Fe16O27 hexaferrites prepared by stearic acid gel route in presence of SDS surfactant - Joyania, R. B.; Khomane, Ramdas B.; Chauhan, C. C.; Kulkarni, B. D. (Synthesis and Reactivity in Inorganic Metal-Organic and Nano-Metal Chemistry, 2008)
The preparation of BaCa2Fe16O27 hexaferrite powders by a stearic acid gel method with SDS surfactant has been investigated at various sintering temperatures. The samples were characterized by X-ray diffraction, scanning electron microscopy (SEM), TGA, FTIR and vibrating sample magnetometer (VSM). The effect of sintering temperature on properties of BaCa2Fe16O27 hexaferrites was studied. In presence of sodium dodecyl sulfate (SDS) surfactant, the magnetic parameters, like saturation magnetization, coercivity and remanent magnetization, have been calculated from hysteresis loop.
Symposium on New Routes to Inorganic Materials, Films and Nanocrystals held at ICMAT 2007, Singapore, SINGAPORE, JUL 01-06, 2007
Keywords: BaCa2Fe16O27; magnetic properties; stearic acid gel method